Training pedagogical competence for teachers: a bibliometric analysis using the Scopus database - Thi Nguyen, Viet Nga; Lien Lai, Phuong (Institute of Advanced Engineering and Science, 2025)
Pedagogical competence training for teachers is an intensive training process to improve teachers’ knowledge, skills, and teaching ability. The change in teaching and research and the development of science and technology have affected the training of pedagogical competency for teachers in many countries. An analysis of the publications related to these paints a general picture of significant trends and contributions by scientists and has implications for policymakers and researchers alike. The study used bibliographic analysis to analyze 344 documents extracted from the Scopus database related to pedagogical competence training for teachers. The results show that the number of studies on this topic increased sharply, especially from 2015 to 2022 and mainly from studies in the United States and developed countries. In addition, the most concerning issues are higher education, professional development, and teacher training. Policymakers and researchers can find prominent authors, influential studies, and regularly published journals on teacher training to read and write about. Further studies based on a combination of bibliographic analysis and other methods may help paint a deeper picture of the research findings on this topic.